Ratio Decidendi, Agreement, Againts The Decision of MA No. 601K/PDT/2015 in The Case of Agreements that do not use Indonesian - Jeremy Emmanuel Purba (Jurnal Penelitian Hukum De Jure, 2021)
The Supreme Court’s decision in the case of an agreement between investors who enter into an agreement using English is contrary to the agreement of the parties. Changes to the agreement may be detrimental to investors in Indonesia, who must amend the agreement previously made in English. The research method based on the data needed in this research is secondary data obtained through literature study in the form of laws and descriptive analysis, namely analyzing the laws and regulations. The loan agreement between PT. BKP and Nine AM, Ltd. should not be null and void. The judge’s interpretation of a lawful cause is wrong because a lawful cause refers the contents of the loan agreement. The government should be firm in determining a sanction if there is a violation of the law. This is intended so that judges are not wrong in applying regulations so that they do not produce decisions that can harmcertain parties.